The “online reputation” of immunization information online - Cuesta Cambra, Ubaldo; Gaspar Herrero, Sandra (Historia y Comunicación Social, 2014)
The aim of this research was to: 1) identify sites, blogs and digital media in dealing with vaccines and build a taxonomy 2) monitor daily the speech analyzing qualitative and quantitative variables 3) to develop a quantitative and qualitative discussions terms of the “Theory of Frame” (Entman, 1993). The results allow obtaining a precise and objective classification of contemporary social discourse on vaccines, knowing the issues, canals, etc.. most relevant, confirming the use of negative stereotypes by certain issuers of low social impact (anti-vaccine) versus a more rigorous approach prevalent.